PEMIKIRAN FIQIH AL-SAYYID SABIQ DALAM BIDANG IBADAH - Aibdi Rahmat (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2009)
Abstract: The Islamic Legal Thought of Sayyid Sabiq in Religious Observance. Although Islam allows and even encourages ijtihâd, the fields of this undertaking is generally understood as limited to certain aspects of Islam and only when there are no religious texts available. Rituals (‘ibâdah) is generally considered as a field where al-Qur’an and hadis provide detailed instructions, thus there is no need for ijtihad in this field. Al-Sayyid Sabiq, however, insists that even on this field there are still rooms for ijtihad. He comes with some examples where one could not find specific instruction from Al-Qur’an and Hadith. This article is an analysis of the position of this particular intellectual on the topic.Kata Kunci: fiqh, air musta‘mal, wudhu’, shalat